Nonlinear pulse propagation for novel optical solitons modeled by Fokas system in monomode optical fibers - Tarla, Sibel; Ali, Karmina K.; Sun, Tian-Chuan; Yilmazer, Resat; Osman, M. S. (Elsevier, 2022)
In this study, the Fokas system which represents the spread of irregular pulse in monomode optical fibers is investigated via the Jacobi elliptic function expansion (JEFE) method. This method is the most powerful technique to explore solutions for a wide range of various models. As a result, different solutions such as dark-bright, singular, bright, Jacobi elliptic function, and exponential solutions are obtained. In addition, 3D and 2D graphics for the obtained solutions are investigated with the assist of a computer program by assigning particular values to the parameters involved.
Keywords: Exact solutions; Fokas System; JEFE method; Complex wave structures